Prevalence and factors associated with overweight and obesity among Malaysian post graduate students in a public university - Abba, Shaima’u Kabir; Md Said, Salmiah; Ismail, Suriani (Community Health Society Malaysia, 2014)
Overweight and obesity is a major public health problem globally because they increase the burden of non-communicable diseases such as cardiovascular diseases, and cancers. Many studies on overweight and obesity in the universities focused on the undergraduate students and there is little information on post-graduate students. Thus, this study aimed at determining the prevalence and factors associated with overweight and obesity among Malaysian post graduate students in a public university. A cross sectional study was conducted among 945 post-graduate students from six faculties using cluster sampling technique. Information on socio-demographic, level of physical activity, smoking and alcohol intakes, and drug history were obtained using self-administered questionnaire. Body weight and height were measured twice and their means were used in the calculation of body mass index. Overweight and obesity were classified based on World Health Organization cut-off points. The overall prevalence of overweight and obesity were 23.1% (95% CI: 20.4%, 25.8%), and 8.9% (95% CI: 7.1%, 10.7%) respectively. The independent factors of overweight and obesity were male (AOR= 1.49; 95% CI: 1.07,2.08), aged group of 30 to 34 years (AOR= 2.53; 95% CI: 1.59, 4.04); and 35 to 39 years (AOR=2.05; 95% CI: 1.15, 3.64); other ethnic group (AOR=5.03; 95% CI: 1.75, 14.48); low and moderate physical activity (AOR=11.16; 95% CI 4.67, 26.70) and (AOR=3.16; 95% CI: 1.31, 7.62). In conclusion, almost one third of students were overweight and obese. The only modifiable factor of overweight and obesity in this study was moderate and low level of physical activity.